Village Officials' Communication Strategy for Community Empowerment: Productive Economic Enterprise Development in Cinangka Village, Ciampea (Oratio Directa, 2022)
This study examines the communication strategy of village officials in developing productive economic enterprises in Cinangka Village, Ciampea District, Bogor Regency. It uses a qualitative descriptive approach with interviews, observation, document review, and componential analysis. Informants included the village head, village officials, the Village Consultative Body, and community members, although the source does not report their number. The empowerment program focused on culinary and handicraft skills through biweekly training, counseling, staged capital support, and the planned development of a shared e-commerce website. The communication strategy relied primarily on face-to-face persuasion initiated through village deliberations. Officials and facilitators adjusted messages to residents' needs, used direct dialogue, received feedback on business constraints, and sought changes in knowledge, attitudes, and participation. The source reports different responses between younger and adult participants, but these differences cannot be generalized because participant characteristics and comparative evidence are insufficiently documented. The program demonstrates the value of participatory planning and personal communication, while also revealing the need for transparent participant selection, measurable business outcomes, youth-sensitive facilitation, and clear management of the planned digital marketplace.
Keywords: Communication strategy; Community empowerment; Productive economic enterprises; Persuasive communication; Village government